2021
DOI: 10.21037/tlcr-21-39
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for advanced-stage non-small cell lung cancer: lobectomy or sub-lobar resection?

Abstract: Background: Metastatic non-small cell lung cancer (NSCLC) has many comorbidities, such as chronic obstructive pulmonary disease, coronary heart disease, and older age-related comorbidities. A survival benefit was observed in such patients who underwent surgery for selected oligometastatic disease. However, to the best of our knowledge, there is no evidence to support whether lobectomy (compared with sub-lobar resection) would further prolong these patients' lives.Methods: Patients with metastatic NSCLC who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The LND was performed on the basis of surgery; therefore, the relation between LND and surgery is worth discussing. The previous studies showed that surgery was associated with more survival benefits in patients with stage IV NSCLC with lower T stage as T1-2 ( 26 ) compared with those with higher T, and lobectomy might have better survival versus SLR ( 33 ). This present study suggests LND might benefit stage IV NSCLC patients who underwent surgery with higher T stage like T3-4 and those who received SLR, as compared with the non-LND.…”
Section: Discussionmentioning
confidence: 99%
“…The LND was performed on the basis of surgery; therefore, the relation between LND and surgery is worth discussing. The previous studies showed that surgery was associated with more survival benefits in patients with stage IV NSCLC with lower T stage as T1-2 ( 26 ) compared with those with higher T, and lobectomy might have better survival versus SLR ( 33 ). This present study suggests LND might benefit stage IV NSCLC patients who underwent surgery with higher T stage like T3-4 and those who received SLR, as compared with the non-LND.…”
Section: Discussionmentioning
confidence: 99%
“…10 which may be challenging to deliver to such patients. 14,24,28,[32][33][34][35] In real-life studies, patients with NSCLC usually tend to be older and have a wide range of age-related comorbidities, such as chronic obstructive pulmonary disease and coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, growing evidence supports the substantial importance of tumor resection in locally advanced NSCLC patients, which may contribute to better survival outcomes 11,14,22,23 . Multiple studies have confirmed a higher 5‐year disease‐free survival in patients who underwent chemoradiotherapy plus surgery or chemotherapy plus surgery versus standard definitive chemoradiotherapy in the OS 11,24–28 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations